2017
DOI: 10.1038/srep42715
|View full text |Cite
|
Sign up to set email alerts
|

Aging transition by random errors

Abstract: In this paper, the effects of random errors on the oscillating behaviors have been studied theoretically and numerically in a prototypical coupled nonlinear oscillator. Two kinds of noises have been employed respectively to represent the measurement errors accompanied with the parameter specifying the distance from a Hopf bifurcation in the Stuart-Landau model. It has been demonstrated that when the random errors are uniform random noise, the change of the noise intensity can effectively increase the robustnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In an effort to understand the origin of this transition-which does not appear to be the consequence of a simple majority rule-a number of variations of the initial model [1] have been studied, by incorporating distributed time delays [4,5], by varying the network topology [6,7], or by introducing heterogeneity in the parameters [8,9] as well as by including noise [10]. The nature of the coupling between the oscillators-whether through similar or dissimilar variables [11,12]-has also been explored in some detail over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to understand the origin of this transition-which does not appear to be the consequence of a simple majority rule-a number of variations of the initial model [1] have been studied, by incorporating distributed time delays [4,5], by varying the network topology [6,7], or by introducing heterogeneity in the parameters [8,9] as well as by including noise [10]. The nature of the coupling between the oscillators-whether through similar or dissimilar variables [11,12]-has also been explored in some detail over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been identified that the addition of asymmetry or feedback parameter enhances the dynamical robustness in an aging network [38,39]. Effects of time-delay or random errors on the aging behavior have also been studied by varying the proportion of inactive oscillators [40,41]. Very recently, the aging transition in weighted homogeneous and heterogeneous networks has also been reported [42].…”
Section: Introductionmentioning
confidence: 99%
“…Addition of supporting oscillators to damaged networks can develop the survivability of the networks [71]. Random errors in the parameters of the local dynamical units can also bring global rhythmicity back [72]. Recently, the authors of [73] studied that a global feedback from all the nodes helps in augmenting dynamical persistence.…”
Section: Introductionmentioning
confidence: 99%